Nanostructured fusiform hydroxyapatite particles precipitated from aquaculture wastewater - Enrico Andreoli (Chemosphere, 2017)
The present work represents a new approach for the isolation of uniform nano particulate hydroxyapatite (HAp). The chemical characterization of a calcium phosphate product obtained from industrial trout farm aquaculture wastewater by two different routes, washing either with a basic aqueous medium (washNaOH) or followed by a further washing with ethanol (washEtOH), is explored. Characterization of the isolated materials includes morphology studies (SEM and TEM), structural (XRD, electron diffraction), compositional (EDX) and thermogravimetric analysis (TGA). The obtained products are a mixture of different compounds, with hydroxyapatite the predominant phase. The morphology is unusually nanometric size with fusiform shaped particles, such characteristics are ordinarily only obtained by synthetic routes. This process of phosphate precipitation represents a unique self-sufficient process to be compared to conventional chemical or biological practices for precipitating phosphate.